Through proxy and scale: How measurement choices shape narratives of shoreline change and vulnerability across embayed sandy beaches of southern Ireland - Emma Chalençon; Mélanie Biausque; Fiona Cawkwell; Rory Scarrott; Larissa Macedo Cruz de Oliveira; Ayse Nur Karayel; Aaron Lim; Michael O'Shea; Jimmy Murphy (Marine Geology, 2026)

Seeing the whole coastline: Building and testing a comprehensive sustainable coastal vulnerability index - Emma Chalençon; Fiona Cawkwell; Michael O'Shea; Jimmy Murphy (Applied Geography, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sensory profile and drivers of liking of grass-fed and total mixed ration butters - Lauren McGuinness; Mark Timlin; Sean A. Hogan; Tom F. O'Callaghan; John P. Murphy; Deirdre Hennessy; Michael O'Donovan; Ellen Fitzpatrick; Kieran McCarthy; E. Dolores O'Riordan; Andre Brodkorb; Emma L. Feeney (Food Quality and Preference, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Engaging citizens from low-income communities in transport planning: experiences from peer research studies conducted in three African cities - Gina Porter; Bradley Rink; Emma Murphy; Fatima Adamu; Plangsat Bitrus Dayil; Sam Clark; Bulelani Maskiti; Claire Dungey; Ariane de Lannoy (Journal of Transport Geography, 2026)

Planar chromatography method development for the herbal metabolomic study on Achillea millefolium (Asteraceae) - Simon J. Jackson; Paolo Goi; Dario Fornara; Tim Yeomans; Katie Shiels; Emma Murphy (Phytochemistry Letters, 2025)

Using low levels of antimicrobials and antiseptics as elicitors for environmental isolates to activate or re-activate antimicrobial producing biosynthetic gene clusters - Amy McLeman; Emma Murphy; Adam P. Roberts (Phytochemistry Letters, 2025)

Less is more; intermediate oiling has a greater impact than heavy oiling on feather permeability in Northern Gannets (Morus bassanus) - Nina Rogerson; Mark Jessopp; Emma Murphy (Marine Biology, 2025)
Northern gannets are the largest migratory seabird in the Northern Atlantic and are vulnerable to oil pollution as a result of industrialisation spreading to marine environments. This study experimentally investigated the effect of crude oil on gannet feathers under laboratory conditions, with respect to (a) mass accumulation from contact with oil on water surface, and (b) water permeability of feathers following oiling. Gannet feather mass increased by as much as 945% following heavy oil contact, with even light oiling increasing feather mass by 93.4% on average. Intermediate oiling corresponding to thin sheens on the water surface had the most damaging effect on feather permeability, letting water through feathers almost twice as quickly as controls, while thick crude oil slicks had the opposite effect, slowing water permeability 1.48 times compared to controls. Drastically lower water permeability in gannet feathers, compared to previously published data from Manx shearwaters, was explained by a denser arrangement of feather barbs and barbules in gannets, effectively demonstrating how seabirds differ in their vulnerability to oiling. This study suggests that a species’ susceptibility to the impacts of oil pollution is strongly related to its feather structure, which is linked to individual foraging strategies, with potential consequences for survival and breeding success affecting populations.

Anything you can eat, I can eat better: Evidence of generalism from species to individual level in an insect herbivore - Mattheau S. Comerford; William Maguire; Leah Murphy; Emma Schneider; Mayra C. Vidal (Ecology, 2025)
Most insect herbivores specialize on a few host plants; however, there are a minority of highly generalized species capable of feeding on hundreds of hosts. Generalism could emerge as a property of the species as a whole, while individuals would still exhibit greater specialization at more specific organizational levels. Yet, we lack studies with generalist insect herbivores directly testing this prediction. Here, we test if the highly generalized fall webworm ( Hyphantria cunea ) maintains its broad diet through specialization at the population, maternal genotype, or individual level. We reared two populations and multiple matrilines on either a static or rotating diet of four host plants. We found that both populations survived and pupated on all hosts, suggesting population‐level generalization. We found evidence for generalization at the genotype level, as maternal genotypes did not vary in performance rankings across host plants. Finally, we found generalism at the individual level, as individuals reared on a rotating diet had no difference or showed intermediate performance to those reared on static diets. Overall, we found support for the maintenance of generalism across all levels, suggesting that generalist species need not be locally specialized to maintain their extremely broad diet.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Can recovered road sweeping wastes provide a soil or soil amendment alternative? An investigation of temporal variability of physico-chemical parameters - Daniel Niepsch; Edward Randviir; Rebecca Murphy-Peers; Emma Coulthard; David Hackett; David McKendry; David Megson (Journal of Environmental Management, 2025)

Exploring the role of polysaccharides from macroalgae in shaping gut microbiome and promoting anti-obesity outcomes - Mehdi Amiri Goushki; Zahra Kharat; Gustavo Waltzer Fehrenbach; Emma J. Murphy; Declan Devine; Noel Gately; Evert Fuemayor (Food Hydrocolloids, 2025)

Young women's travel safety and the journey to work: Reflecting on lived experiences of precarious mobility in three African cities (and the potential for transformative action) - Gina Porter; Emma Murphy; Fatima Adamu; Plangsat Bitrus Dayil; Claire Dungey; Bulelani Maskiti; Ariane de Lannoy; Sam Clark; Hadiza Ahmad; Mshelia Jummai Yahaya (Journal of Transport Geography, 2025)

The effect of bovine diets and stages of lactation on vitamin K content in butter and Cheddar cheese - Sitong Zhou; Jean-Christophe Jacquier; Raquel Cama-Moncunill; Hannah Furlong; Gabriela Gonzales Castillo; Peter Dunne; Mark Timlin; Deirdre Hennessy; Michael O’Donovan; Kieran McCarthy; Tom F. O’Callaghan; John P. Murphy; et al. (International Dairy Journal, 2025)

Comprehensive analysis and assessment of exposure to enteric viruses and bacteria in shellfish - Gustavo Waltzer Fehrenbach; Emma Murphy; Robert Pogue; Frank Carter; Eoghan Clifford; Ian Major (Marine Environmental Research, 2024)

Impact of feeding regimes and lactation stage on sensory attributes of Cheddar cheese - Lauren McGuinness; Mark Timlin; John P. Murphy; Deirdre Hennessy; Ellen Fitzpatrick; Kieran McCarthy; Michael O'Donovan; Tom F. O'Callaghan; Kieran N. Kilcawley; E. Dolores O'Riordan; Andre Brodkorb; Jeremiah J. Sheehan; et al. (Food Research International, 2024)

Environmental and behavioural drivers of Antarctic krill distribution at the South Orkney Islands: A regional perspective - Emma F. Young; Sally E. Thorpe; Angelika H.H. Renner; Eugene J. Murphy (Journal of Marine Systems, 2024)

Predictions of PFAS regional-scale atmospheric deposition and ambient air exposure - Emma L. D'Ambro; Benjamin N. Murphy; Jesse O. Bash; Robert C. Gilliam; Havala O.T. Pye (Science of The Total Environment, 2023)

Reproductive biology of male common dolphins (Delphinus delphis) in New Zealand waters - Emily I. Palmer; Emma L. Betty; Sinéad Murphy; Matthew R. Perrott; Adam N. H. Smith; Karen A. Stockin (Marine Biology, 2023)
Reproductive parameters were assessed in 64 male common dolphins ( Delphinus delphis ) examined post-mortem from strandings and bycatch in New Zealand between 1999 and 2020. The stages of male sexual maturation were assessed using morphological measurements and histological examination of testicular tissue. Age was determined via growth layer groups (GLGs) in teeth. The average age (ASM) and length (LSM) at attainment of sexual maturity were estimated to be 8.8 years and 198.3 cm, respectively. Individual variation in ASM (7.5–10 years) and LSM (190–220 cm) was observed in New Zealand common dolphins. However, on average, sexual maturity was attained at a similar length but at a marginally younger age (< 1 year) in New Zealand compared to populations in the Northern Hemisphere. All testicular variables proved better predictors of sexual maturity compared to demographic variables (age and total body length), with combined testes weight the best outright predictor of sexual maturity. Reproductive seasonality was observed in male common dolphins, with a significant increase in combined testes weight in austral summer. This aligns with most other studied populations, where seasonality in reproduction is typically observed. Given the known anthropogenic impacts on New Zealand common dolphins, we recommend that these findings be used as a baseline from which to monitor population-level changes as part of conservation management efforts.

The lived experiences of women workers in Africa's transport sector: Reflections from Abuja, Cape Town and Tunis - Gina Porter; Emma Murphy; Fatima Adamu; Plangsat Bitrus Dayil; Saerom Han; Claire Dungey; Bulelani Maskiti; Ariane de Lannoy; Sam Clark; Edward O'Connor; Shadi Ambrosini (Journal of Transport Geography, 2023)

Insights into plasma-catalytic nitrogen fixation from catalyst microanalysis and chemical kinetics modelling - Jing Sun; Tianqi Zhang; Jungmi Hong; Rusen Zhou; Hassan Masood; Renwu Zhou; Anthony B. Murphy; Kostya Ken Ostrikov; Patrick J. Cullen; Emma C. Lovell; Rose Amal; Ali Rouhollah Jalili (Chemical Engineering Journal, 2023)

The faunal Ponto-Caspianization of central and western European waterways - Ismael Soto; Ross N. Cuthbert; Anthony Ricciardi; Danish A. Ahmed; Florian Altermatt; Ralf B. Schäfer; Gaït Archambaud-Suard; Núria Bonada; Miguel Cañedo-Argüelles; Zoltán Csabai; Thibault Datry; Jaimie T. A. Dick; et al. (Biological Invasions, 2023)
As alien invasive species are a key driver of biodiversity loss, understanding patterns of rapidly changing global species compositions depends upon knowledge of invasive species population dynamics and trends at large scales. Within this context, the Ponto-Caspian region is among the most notable donor regions for aquatic invasive species in Europe. Using macroinvertebrate time series collected over 52 years (1968–2020) at 265 sites across 11 central and western European countries, we examined the occurrences, invasion rates, and abundances of freshwater Ponto-Caspian fauna. We examined whether: (i) successive Ponto-Caspian invasions follow a consistent pattern of composition pioneered by the same species, and (ii) Ponto-Caspian invasion accelerates subsequent invasion rates. In our dataset, Ponto-Caspian macroinvertebrates increased from two species in 1972 to 29 species in 2012. This trend was parallelled by a non-significant increasing trend in the abundances of Ponto-Caspian taxa. Trends in Ponto-Caspian invader richness increased significantly over time. We found a relatively uniform distribution of Ponto-Caspian macroinvertebrates across Europe without any relation to the distance to their native region. The Ponto-Caspian species that arrived first were often bivalves (46.5% of cases), particularly Dreissena polymorpha , followed secondarily by amphipods (83.8%; primarily Chelicorophium curvispinum and Dikerogammarus villosus ) . The time between consecutive invasions decreased significantly at our coarse regional scale, suggesting that previous alien establishments may facilitate invasions of subsequent taxa. Should alien species continue to translocate from the Ponto-Caspian region, our results suggest a high potential for their future invasion success highly connected central and western European waters. However, each species’ population may decline after an initial ‘boom’ phase or after the arrival of new invasive species, resulting in different alien species dominating over time.

Neurodevelopmental outcomes in children and adults with Fetal Valproate Spectrum Disorder: A contribution from the ConcePTION project - Matthew Bluett-Duncan; Denise Astill; Rana Charbak; Jill Clayton-Smith; Susan Cole; Penny A. Cook; Jo Cozens; Karen Keely; Jacki Morris; Raja Mukherjee; Emma Murphy; Peter Turnpenny; et al. (Neurotoxicology and Teratology, 2023)

Pulsed ultraviolet (PUV) disinfection of artificially contaminated seawater seeded with high levels of pathogen disease indicators as an alternative for the shellfish industry depuration systems - Gustavo Waltzer Fehrenbach; Emma Murphy; Robert Pogue; Frank Carter; Eoghan Clifford; Ian Major; Neil Rowan (Environmental Science and Pollution Research, 2023)
The increase in pathogen levels in seawater threatens the safety of entire aquatic ecosystems. Foodborne pathogens can potentially accumulate in shellfish, especially in filter feeders such as bivalves, requiring an efficient depuration process before consumption. Alternative approaches to promote a cost-efficient purge at depuration plants are urgently needed. A small prototype pulsed ultraviolet (PUV) light recirculation system was designed, and its depuration potential was tested in a seawater matrix artificially contaminated with high levels of microbial pathogens Escherichia coli , Staphylococcus aureus , Salmonella typhimurium , Bacillus cereus and Candida albicans . The analysis of treatment parameters including voltage, number of pulses and duration of treatment was performed to ensure the highest reduction in contaminant levels. Optimal PUV disinfection was attained at 60 pulses/min at 1 kV for 10 min (a UV output of 12.9 J/cm 2 ). All reductions were statistically significant, and the greatest was observed for S. aureus (5.63 log 10 ), followed by C. albicans (5.15 log 10 ), S. typhimurium (5 log 10 ), B. cereus (4.59 log 10 ) and E. coli (4.55 log 10 ). PUV treatment disrupted the pathogen DNA with the result that S. aureus , C. albicans and S. typhimurium were not detectable by PCR. Regulations were reviewed to address the applicability of PUV treatment as a promising alternative to assist in the reduction of microbial pathogens at depuration plants due to its high efficiency, short treatment period, high UV dose and recirculation system as currently employed in shellfish depuration plants.

Profile likelihood-based parameter and predictive interval analysis guides model choice for ecological population dynamics - Matthew J. Simpson; Shannon A. Walker; Emma N. Studerus; Scott W. McCue; Ryan J. Murphy; Oliver J. Maclaren (Mathematical Biosciences, 2023)

Reproductive biology of female common dolphins (Delphinus delphis) in New Zealand waters - Emily I. Palmer; Emma L. Betty; Sinéad Murphy; Matthew R. Perrott; Adam N. H. Smith; Karen A. Stockin (Marine Biology, 2022)
Reproductive biology was assessed in 106 female common dolphins ( Delphinus delphis ) examined post-mortem from stranding and bycatch events along the New Zealand coastline between 1997 and 2019. The average age (ASM) and length (LSM) at sexual maturity was estimated at 7.5 years and 183.5 cm, respectively. The total number of corpora in mature individuals increased with age and appeared to persist throughout life. Ovarian asymmetry was apparent, with the left ovary displaying higher rates of ovulation, and a maximum of 19 corpora recorded for a 24-year-old female. The estimated ovulation and annual pregnancy rates for mature females were 0.39 year −1 and 30%, respectively. Conception and calving occurred year-round, with a weak seasonal increase observed in late austral spring and early austral summer. As these data did not clearly show whether seasonality was present, the gestation, lactation, and resting periods were calculated as either 12.6 or 12.8 months based on the presence/absence of seasonality, respectively. Similarly, calving interval ranged from 3.15 to 3.2 years, depending upon whether seasonality was considered. The estimated LSM of the New Zealand population aligns with other populations globally, although the estimated ASM is younger by approximately 6 months. Other reproductive parameters align with Northern Hemisphere populations, although demonstrate variation, which may reflect adaptations to local conditions such as water temperature and prey availability. As the species is subject to anthropogenic impacts including pollution and bycatch, we suggest our findings be used as a baseline with which to monitor trends in population parameters.

Investigating the importance of B cells and antibodies during Trichuris muris infection using the IgMi mouse - Rinal Sahputra; Emma A Murphy; Ruth Forman; Iris Mair; Muhammad Z. H. Fadlullah; Ari Waisman; Werner Muller; Kathryn J. Else (Journal of Molecular Medicine, 2020)
The IgMi mouse has normal B cell development; its B cells express an IgM B cell receptor but cannot class switch or secrete antibody. Thus, the IgMi mouse offers a model system by which to dissect out antibody-dependent and antibody-independent B cell function. Here, we provide the first detailed characterisation of the IgMi mouse post- Trichuris muris ( T. muris ) infection, describing expulsion phenotype, cytokine production, gut pathology and changes in T regulatory cells, T follicular helper cells and germinal centre B cells, in addition to RNA sequencing (RNA seq) analyses of wild-type littermates (WT) and mutant B cells prior to and post infection. IgMi mice were susceptible to a high-dose infection, with reduced Th2 cytokines and elevated B cell-derived IL-10 in mesenteric lymph nodes (MLN) compared to controls. A low-dose infection regime revealed IgMi mice to have significantly more apoptotic cells in the gut compared to WT mice, but no change in intestinal inflammation. IL-10 levels were again elevated. Collectively, this study showcases the potential of the IgMi mouse as a tool for understanding B cell biology and suggests that the B cell plays both antibody-dependent and antibody-independent roles post high- and low-dose T. muris infection. Key messages During a high-dose T. muris infection, B cells are important in maintaining the Th1/Th2 balance in the MLN through an antibody-independent mechanism. High levels of IL-10 in the MLN early post-infection, and the presence of IL-10-producing B cells, correlates with susceptibility to T. muris infection. B cells maintain gut homeostasis during chronic T. muris infection via an antibody-dependent mechanism.

Adaptable Monitoring Package Development and Deployment: Lessons Learned for Integrated Instrumentation at Marine Energy Sites - Brian Polagye; James Joslin; Paul Murphy; Emma Cotter; Mitchell Scott; Paul Gibbs; Christopher Bassett; Andrew Stewart (Journal of Marine Science and Engineering, 2020)
Integrated instrumentation packages are an attractive option for environmental and ecological monitoring at marine energy sites, as they can support a range of sensors in a form factor compact enough for the operational constraints posed by energetic waves and currents. Here we present details of the architecture and performance for one such system—the Adaptable Monitoring Package—which supports active acoustic, passive acoustic, and optical sensing to quantify the physical environment and animal presence at marine energy sites. we describe cabled and autonomous deployments and contrast the relatively limited system capabilities in an autonomous operating mode with more expansive capabilities, including real-time data processing, afforded by shore power or in situ power harvesting from waves. Across these deployments, we describe sensor performance, outcomes for biological target classification algorithms using data from multibeam sonars and optical cameras, and the effectiveness of measures to limit biofouling and corrosion. On the basis of these experiences, we discuss the demonstrated requirements for integrated instrumentation, possible operational concepts for monitoring the environmental and ecological effects of marine energy converters using such systems, and the engineering trade-offs inherent in their development. Overall, we find that integrated instrumentation can provide powerful capabilities for observing rare events, managing the volume of data collected, and mitigating potential bias to marine animal behavior. These capabilities may be as relevant to the broader oceanographic community as they are to the emerging marine energy sector.

Using emerging hot spot analysis of stranding records to inform conservation management of a data-poor cetacean species - Emma L. Betty; Barbara Bollard; Sinéad Murphy; Mike Ogle; Hannah Hendriks; Mark B. Orams; Karen A. Stockin (Biodiversity and Conservation, 2020)

Erratum to: Trends in the classical biological control of insect pests by insects: an update of the BIOCAT database - Matthew J. W. Cock; Sean T. Murphy; Moses T. K. Kairo; Emma Thompson; Rebecca J. Murphy; Antonio W. Francis (BioControl, 2017)

Trends in the classical biological control of insect pests by insects: an update of the BIOCAT database - Matthew J. W. Cock; Sean T. Murphy; Moses T. K. Kairo; Emma Thompson; Rebecca J. Murphy; Antonio W. Francis (BioControl, 2016)

Mcl-1 is vital for neutrophil survival - Mark P. Murphy; Emma Caraher (Immunologic Research, 2015)

Microbial biotransformation of aryl sulfanylpentafluorides - Emma Kavanagh; Michael Winn; Cliona Nic Gabhann; Neil K. O’Connor; Petr Beier; Cormac D. Murphy (Environmental Science and Pollution Research, 2014)

Impulsive behaviour induced by both NMDA receptor antagonism and GABAA receptor activation in rat ventromedial prefrontal cortex - Emily R. Murphy; Anushka B. P. Fernando; Gonzalo P. Urcelay; Emma S. J. Robinson; Adam C. Mar; David E. H. Theobald; Jeffrey W. Dalley; Trevor W. Robbins (Psychopharmacology, 2012)